RETRACTED: Optimal utilization of multicore processors with PLINQ in .NET applications - Zaripova Rimma; Aygumov Timur; Kovrizhnykh Olga; Akhmetshin Dinar; Nuriev Marat (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001